Pengaruh Pendidikan Kewirausahaan Terhadap Minat Berwirausaha - Rembulan, Glisina Dwinoor; Fensi, Fabianus (Universitas Bunda Mulia, 2017)
Central Bureau of Statistics (BPS) explained that from 2010-2013 Micro Small and Medium Enterprises (MSMEs) in Indonesia has increased. This explains that interest in entrepreneurship in Indonesia still become a trend that gets attention for the people of Indonesia. The government's concern in the field of entrepreneurship is increasingly directed in various business actors, one of them is the young generation. This is in accordance with the government program in 2017 where the launch of Beginner Entrepreneurship (WP). This explains that the opportunity to start a business at a young age is no longer an obstacle in view of the support from the government that participated in encouraging the new WP in Indonesia. Educational institutions can be a training place for entrepreneurship incubation for students. Encouragement through the role of courses in the institution should be able to walk in harmony. Readiness of students is not uncommon to be a barrier to start a business. This study aims to explain whether there is an influence between the factors of encouragement of educational institutions and entrepreneurship courses to entrepreneurial interests for students. By using SPSS and error rates of 5%, this results that both the educational institution and the role of entrepreneurship courses partially affect student entrepreneurship interests. This study has limitation on the use of sample quantities and independent variables that still tend to be within a small range. Therefore, next researches may consider this as input.Keywords: encouragement, institution, education, intention, entrepreneur